DINAMIKA PERBATASAN WILAYAH LAUT DI SELAT MALAKA SINGAPURA - Awani Irewati (Pusat Penelitian Politik, 2011)
Strait ofMalacca Singapore is still taken into account in international trade and shipping lane Externally three littoral states Malaysia Indonesia and Singapore are parties that govern security and safety ofshipping lane in Strait ofMalacca Singapore according to traffic separation scheme TSS and the Mandatory Ship Reporting System in the Straits ofMalacca and Singapore Straitrep Strait ofMalacca Singapore has different meaningforthe three littoral states especially between Singapore on one side and Malaysia plus Indonesia on the other sideSignificance ofStrait ofMalacca Singaporefor Singapore is caught throughfree transit approach while Malaysiaand Indonesia get its significance through innocent passage approach But there is still another transit passageapproach that can become middle way in solving the differences Even so internally the three littoral states havenot yet solve their maritime boundary problems thoroughly Settlement ofmaritime boundary issues and agreementamong the three countries are very important because the boundary is located in international trade andshipping lane In the future the meaning ofStrait ofMalacca Singapore for the three countries is still very important fortheir national interest and the problem that exist among them is part ofdynamics ofStrait ofMalacca Singaporeneighbourhood